An integrated solar evaporator with multilevel hierarchy and multifunctional properties for efficient and salt fouling-resistant desalination. Issue 45 (11th November 2022) - Yang, Zhi; Chen, Lei; Yang, Kaijie; Chen, Cheng; Zhang, Yuyao; Li, Shan; Chu, Chiheng; Zhu, Xiaoying; Chen, Baoliang
Abstract : A hierarchy is integrated into the solar evaporator and triggers multifunctional properties, by which salt-resistant desalination is achieved without sacrificing the energy efficiency even in hypersaline solutions (83–93% in 3.5–25 wt% brine). Abstract : Solar desalination is regarded as a promising technology for addressing severe freshwater scarcity, yet its long-term performance is challenged by salt fouling. Here, we develop an integrated solar evaporator with a hierarchy composed of a porous melamine foam core (MF) as a framework, black graphene oxide (GO) nanosheets as the solar absorption layer, and a positively charged poly(ethyleneimine) (PEI) shell as the salt rejecting layer. The solar evaporator equipped with a macro-, micro-, and nanoscale structure triggers multifunctional properties boosting efficiency and stability in desalinating multiple salinities. The solar evaporator achieves high energy efficiency in pure water and exhibits rather high efficiency under hypersaline conditions (82.8–93.4% in 0–25 wt% brine) compared with the state-of-the-art evaporators. The integral functions of the multiscale hierarchy bring about an optimized solar absorption rate (97.6%), improved photothermal conversion ability (25.0 °C), ultrahigh wettability (0.252 s), and excellent thermal insulation properties (0.0505 W m −1 K −1 ). The multilayer properties were achieved with a neutral core, negatively charged GO interlayer, and positively charged PEI outlayer benefiting salt rejection by the electrostatic repulsion forces. The multiscale structure improves the solar evaporation efficiency by regulating the states of water molecules. This integrated solar evaporator paves a new route for freshwater production from water sources of various salinities.